The impact of climate, socio-political and COVID-19 shocks on Tunisia's potential growth - Kamel Dridi (Graduate Institute of International and Development Studies, 2024)
This study estimated Tunisia's potential growth with a Cobb-Douglas production function using an unobservable component model within structural changes context for the period 1989-2023. It investigated the major shocks' effects on the potential growth and its components. In contrast with most studies, we employed the Beveridge Curve to deduce the natural unemployment rate. In order to obtain a more realistic labor trend. We developed a methodology with which we created an indicator of working hours that considers a representative distribution of employment, in particular by sector, location, and gender. We performed the study in an uncertain environment. Structural changes have an important impact on the major macroeconomic trends. We manipulated these changes using a variety of econometric time series techniques. We performed the Bai-Perron test to detect slight shifts. The results show that for the last 40 years, Tunesia has not been able to maintain high potential production growth rates. The country could not halt the significant deceleration of potential output that began in the 2010s or avoid the negative potential growth differentials by 2020-23. Total factor productivity was insufficient to avoid a permanent slowdown that had become more severe with each shock. Additionally, labor declined in response to decelerating demographic trends and persistent structural unemployment. These issues may remain significant in the future.
Keywords: E22; E23; E24; E27; C82; 330; Potential Growth; Production Function; Unobserved Components Model; structural changes; shocks